The Analysis of Girish Karnad's Hayavadana Play (Journal of the College of Basic Education, 2022)
In the play "Hayavadana", Girish Karnad addresses the issue of Head and Body with the ethical and philosophical side of the problem which raises more significant issues concerning man's existence. He casts the female character in a different style and manner. His female characters are beautiful, intelligent, lively, and more central than male characters in the play " Hayavadana". Karnad through female character introduces the image of nowadays woman who is trapped between two notions, one of them is her search for idealism and completeness and the other is her quest for personal rights in a society dominated by males.Karnad was extremely affected by Indian myths, traditions and history. Thus, he as a creative artist focuses on Indian myths, history, tradition, folklore, legends and theatres. He shapes a new face of modern man fighting for a new prospect with a new character and identity.Hayavadana is a study of man’s search for perfection in every area of universal experience, whether of love, marriage, friendship, motherhood or children, and here where the importance of the research lies. It is a trial to study the notion of identity in a folk story. It is a study of how the desire of a female ruined her and the ones around her by planting the seed of conflict, and this is the focus of the research problem.